Close loop separation process for the recovery of Co, Cu, Mn, Fe and Li from spent lithium-ion batteries - Dutta, Deblina; Kumari, Archana; Panda, Rekha; Jha, Soni; Gupta, Divika; Goel, Sudha; Jha, Manis Kumar (Separation and Purification Technology, 2018)
Lithium-ion batteries (LIBs) are essential energy source used in advanced electronic gadgets for getting constant and continuous power supply. Huge amount of spent LIBs are generated after their end use. LIBs contain metals, organics and plastics which require proper treatment before disposal. Keeping in view of stringent environmental regulations, limited natural resources and energy crisis, adopting recycling will not only protect the environment and pacify the gap between demand and supply but also conserve the natural resources. Present paper reports a complete process for the recycling of LIBs to recover metals and materials as value added products fulfilling zero waste concept. Initially, the spent LIBs were crushed and beneficiated by wet scrubbing process to separate cathodic material, plastic and metallic fractions. The cathodic material contained 20% Co and 2.4% Li along with other impurities (Mn, Fe, Cu). The cathodic material obtained from different LIBs were homogenized and put to leaching studies to optimize various process parameters viz. effect of leachant concentration, temperature, time, etc. About 97% Co and 99.99% Li were leached using 2 M H2SO4 and 10% H2O2 at room temperature, in 2 h maintaining pulp density 75 g/L. Kinetics for leaching of Co fitted well with Chemical reaction control dense constant size cylindrical particles model, i.e. 1 - (1 - X)(1/2) = Kct. The leach liquor obtained was further processed to recover Mn and Fe using (NH4)(2)S2O8 as a precipitant whereas 99.99% Cu was extracted using LIX 84 IC at eq. pH 2, O/A ratio 1/1 and mixing time 5 min. Further, from the leach liquor depleted with Mn, Fe and Cu, similar to 98% Co was extracted using 20% Cyanex 272 at pH 4.8 in 10 min maintaining phase ratio (O/A) 1/1 in two stages, leaving Li in the raffinate. From the pure Co solution, value added products as metal and salt were produced using electrowinning/evaporation/precipitation techniques. The TCLP test of leached residue shows the presence of metals within permissible limit and the effluent generated was treated in an effluent treatment plant (ETP) with standard procedure and recycled to the system. The developed clean process is economical as well as environment friendly and has potential to be translated in industry after scale-up studies.

Characterized constituents of insect herbivore oral secretions and their influence on the regulation of plant defenses - Kallure, Gopal S.; Kumari, Archana; Shinde, Balkrishna A.; Giri, Ashok P. (Phytochemistry, 2022)
For more than 350 million years, there have been ongoing dynamic interactions between plants and insects. In several cases, insects cause-specific feeding damage with ensuing herbivore-associated molecular patterns that invoke characteristic defense responses. During feeding on plant tissue, insects release oral secretions (OSs) containing a repertoire of molecules affecting plant defense (effectors). Some of these OS components might elicit a defense response to combat insect attacks (elicitors), while some might curb the plant defenses (suppressors). Few reports suggest that the synthesis and function of OS components might depend on the host plant and associated microorganisms. We review these intricate plant-insect interactions, during which there is a continuous exchange of molecules between plants and feeding insects along with the associated microorganisms. We further provide a list of commonly identified inducible plant produced defensive molecules released upon insect attack as well as in response to OS treatments of the plants. Thus, we describe how plants specialized and defense-related metabolism is modulated at innumerable phases by OS during plant-insect interactions. A molecular understanding of these complex interactions will provide a means to design eco-friendly crop protection strategies.
Keywords: Effector; Elicitor; Herbivore insects; Oral secretion; Plant defense; Suppressor

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense. - Kallure, Gopal S.; Shinde, Balkrishna A.; Barvkar, Vitthal T.; Kumari, Archana; Giri, Ashok P. (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores' oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenyl-propanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

Characterization of wound-induced electrical signals and reactive oxygen species in chickpea (Cicer arietinum) - Deshpande, Shweta; Pawar, Shivani; Kumari, Archana (Plant Signaling & Behavior, 2025)
Mechanical damage to plants triggers both localized and systemic responses that activate plant defense mechanisms. Early signaling events include calcium (Ca2+) flux, reactive oxygen species (ROS), and electrical alterations. These signals coordinate downstream defense pathways, enabling plant acclimation to biotic stress. Electrical signaling following wounding/herbivory has been extensively studied in Arabidopsis; however, its dynamics in crop plants such as chickpea (Cicer arietinum) are not well understood. The pattern of the SWP in chickpea was similar to that in Arabidopsis but with a longer repolarization phase and was detectable only within the leaflets. The signals generated by damaging the leaflet were more pronounced, propagated bidirectionally and varied between herbivore-susceptible and tolerant chickpea varieties. The SWP duration is correlated with increased expression of AOS and OPR3 transcripts, which are markers of the stress hormone JA. Additionally, ROS production in wounded chickpea leaflets is associated with increased expression of ROS-generating genes. The use of DPI, an inhibitor of NADPH oxidase, which is responsible for ROS production, inhibited SWP, suggesting the crucial role of ROS in wound-induced SWP. This study provides insight into the interplay between wound-induced electrical signaling and ROS production in chickpea and proposes the measurement of electrical signals as a rapid, noninvasive approach for screening crop cultivars for pest susceptibility and tolerance.
Keywords: Chickpea; Electrical signal; Plant defense; ROS; wound